If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + 7(z + -2) = 6z + 1 Reorder the terms: 14 + 7(-2 + z) = 6z + 1 14 + (-2 * 7 + z * 7) = 6z + 1 14 + (-14 + 7z) = 6z + 1 Combine like terms: 14 + -14 = 0 0 + 7z = 6z + 1 7z = 6z + 1 Reorder the terms: 7z = 1 + 6z Solving 7z = 1 + 6z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-6z' to each side of the equation. 7z + -6z = 1 + 6z + -6z Combine like terms: 7z + -6z = 1z 1z = 1 + 6z + -6z Combine like terms: 6z + -6z = 0 1z = 1 + 0 1z = 1 Divide each side by '1'. z = 1 Simplifying z = 1
| 7s+10=4s+4 | | -11=3k+1 | | 49-3x=15x+21 | | 9=-4+3k | | =6v^2+17vp-14p^2 | | 9c-11=6c+25 | | -3=2z+2 | | 4.289x^2-8.578x+3.289=0 | | (3n+4)(2n-3)=0 | | X+22+2x=-9-2x-14 | | 5x-8=-18-5x | | -1=1+z | | X^20=0.1 | | 10=5n+2 | | -.57x=9 | | -6+3a= | | (5b+2)(b+2)=0 | | -3=9n+5 | | -4n+6=-3n-2 | | 6n-3=4n+9 | | 0=2n+12 | | (x+4)(x-3)=0 | | 10=-3+6a | | a=1/2(11+5)4 | | 6x+12=84-10x | | =25t^2+29t+9 | | X+3=48 | | -31=-5y | | 3n+7=2n+12 | | 0=-(2/3)x+30 | | 51=9y | | 4(n+6)+4(n-3)= |